Implementasi Maqasid Al-Shariah dalam Pengembangan Pasar Uang Syariah untuk Kesejahteraan Global - Abd. Hakim (Program Studi Ekonomi Syariah IAIN Parepare, 2025)
Maqasid Al-Shariah plays a strategic role in enhancing the capacity of the ummah to drive intellectual reform and civilizational renewal. This study aims to explore the significance and application of Maqasid Al-Shariah in the development of the Islamic money market as a financial instrument that supports global well-being. Using a qualitative approach based on literature review, the research evaluates the extent to which the principles of Maqasid Al-Shariah, such as the preservation of faith, life, intellect, lineage, and wealth, are integrated into the structure and operations of the Islamic money market. The analysis also identifies potential gaps between the ideal objectives of Shariah and the actual practices in addressing global socio-economic needs. The findings indicate that while there has been progress in formal Shariah compliance, further efforts are needed to ensure that the Islamic money market not only adheres to legal standards but also upholds ethical values and social objectives of Shariah. This study aims to provide insights for optimizing the Islamic money market as an inclusive mechanism that supports sustainable economic development and global prosperity.